2022
DOI: 10.1021/jacs.1c11547
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Localized Plasmons via an Atomistic Approach: Attainment of Site-Selective Activation inside a Single Molecule

Abstract: Chemical reactions such as bond dissociation and formation assisted by localized surface plasmons (LSPs) of noble metal nanostructures hold promise in solar-to-chemical energy conversion. However, the precise control of localized plasmons to activate a specific moiety of a molecule, in the presence of multiple chemically equivalent parts within a single molecule, is scarce due to the relatively large lateral distribution of the plasmonic field. Herein, we report the plasmon-assisted dissociation of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…In addition, on-surface synthesis of carbon-based nanostructures and nanomaterials strongly relies on either thermal excitation or atom manipulation (by means of injecting tunneling electrons) so far, while other extensive excitation sources (such as photo-excitation [169][170][171][172][173] and localized surface plasmons [174][175][176][177] as illustrated in the bottom panel of figure 9) have been much less reported or applied in synthesis. Given that thermal excitation would activate several chemical groups simultaneously, poor reaction selectivity has long been a realistic obstacle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, on-surface synthesis of carbon-based nanostructures and nanomaterials strongly relies on either thermal excitation or atom manipulation (by means of injecting tunneling electrons) so far, while other extensive excitation sources (such as photo-excitation [169][170][171][172][173] and localized surface plasmons [174][175][176][177] as illustrated in the bottom panel of figure 9) have been much less reported or applied in synthesis. Given that thermal excitation would activate several chemical groups simultaneously, poor reaction selectivity has long been a realistic obstacle.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, for pericyclic reactions, selection rules (also known as Woodward Hoffmann rules) indicate that some reactions would be ground state (thermally) allowed, while others would be excited state (photochemically) allowed yet thermally forbidden. Notably, plasmoninduced reactions by confining light at the SPM junction can significantly reduce the energy requirements and facilitate efficient energy conversion with a strong enhancement of the electric field [174,176,177]. Thus, integration of a broader range Moreover, intact deposition of carbon-based molecular precursors or structures is not only prerequisite for on-surface synthesis protocol, but also essential for direct investigation under UHV conditions (cf upper right panel of figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrahigh vacuum (UHV) TERS offers (i) direct visualization of molecular analytes with angstrom spatial resolution and (ii) precise control of the molecular environment. ,,, Using the advantage of UHV-TERS, the Hou and Jiang groups were able to probe weak molecule–substrate interactions and conformations of molecular analytes on the metal surfaces. , Furthermore, Xu and co-workers demonstrated that an electric field of the scanning probe can be used to trigger conformational changes in pentacene adsorbed on Ag(110) . Specifically, the researchers observed α to γ conformational changes in the central benzene ring of pentacene.…”
Section: Future Perspectives: Novel Chemistry and Novel Materialsmentioning
confidence: 99%
“…Using TERS, the researchers demonstrated that α to γ conformational changes were caused by C–H bond breaking at the central benzene ring of pentacene followed by the skeleton deformation of this molecule. Recently, the Jiang group reported that a scanning probe could be used to trigger a dissociation of specific molecular site (C–Si bond) in individual 5,10,15,20-tetrakis­[(trimethylsilyl)­ethynyl]­porphyrin molecules adsorbed on a Cu(100) surface, Figure . To enable such bond scissoring, the scanning probe had to be positioned precisely at the chemical bond atop the molecule.…”
Section: Future Perspectives: Novel Chemistry and Novel Materialsmentioning
confidence: 99%
See 1 more Smart Citation